STUDY AND ANALYSIS OF THE MUSICAL STRUCTURE AND CHARACTERISTICS OF FOLK SONGS OF THE HAN PEOPLE IN LINGYUN, GUANGXI PROVINCE. - Yanfang, Wu; Siriwongsuwan, Rungkiat (วารสารสหวิทยาการสังคมศาสตร์และการสื่อสาร, 2025)
Introduction: The folk songs of the Gaoshan Han ethnic group in Lingyun County, Guangxi Province, China, represent a significant intangible cultural heritage characterized by profound humanistic traditions, diverse musical forms, rich thematic content, vivid lyrical expression, natural rhythmic patterns, and melodious melodies that warrant systematic musicological investigation.Objective: This study examines and analyzes the musical structure and distinctive characteristics of Gaoshan Han folk songs in Lingyun County, Guangxi Province, with particular focus on their digital time-sequence structural functions. Method: A qualitative descriptive research design was employed. Purposive sampling identified key informants including Cao Hongfu (expert in Gaoshan Han music creation and promotion) and Jiang Shui (vocal pedagogy specialist), alongside 20 professional performers from the Xiyuan Art Troupe (Fu Qiuyue, Wu Keying, and colleagues) and folk song enthusiasts (Zhou Xiaoying and others). Data collection integrated document analysis, fieldwork observations, semi-structured interviews, and content synthesis. The analytical framework combined musicology and music aesthetics perspectives to investigate structural patterns. Results: The digital structural expression in Lingyun Gaoshan Han folk songs demonstrates three primary functions: (1) facilitating narrative development within song stories, (2) maintaining architectural simplicity in musical composition, and (3) ensuring efficient oral transmission across generations. Conclusion: The study reveals that the digital time-sequence structure serves as a fundamental mechanism for preserving and transmitting Gaoshan Han folk songs, contributing to the understanding of structural complexity in ethnic minority music traditions and offering insights for intangible cultural heritage conservation strategies.